Double Charge Polarity Switching in Sb‐Doped SnSe with Switchable Substitution Sites. (1st December 2020) - Yamamoto, Chihiro; He, Xinyi; Katase, Takayoshi; Ide, Keisuke; Goto, Yosuke; Mizuguchi, Yoshikazu; Samizo, Akane; Minohara, Makoto; Ueda, Shigenori; Hiramatsu, Hidenori; Hosono, Hideo; Kamiya, Toshio
Abstract: Tin mono‐selenide (SnSe) is one of the most promising thermoelectric materials; however, it experiences difficulty in controlling the carrier polarity, which is inevitable for realizing p‐n homojunction devices. Herein, double switching of charge polarity in (Sn1− x Sb x )Se by varying x is reported; pure SnSe shows p‐type conduction, whereas the polarity of (Sn1− x Sb x )Se switches to n‐type conduction for 0.005 < x  < 0.05, and then re‐switches to p‐type conduction for x  > 0.05. The major Sb substitution site switches from the Se (SbSe ) to Sn site (SbSn ) with increasing x . SbSn (Sb 3+ at Sn 2+ ) works as a donor, but SbSe (Sb 3− at Se 2− ) does not produce a hole because of the Sb–Sb dimer formation. The mechanism of double polarity switching is explained by native p‐type conduction in pure SnSe due to Sn‐vacancy formation, whereas (Sn1− x Sb x )Se exhibits n‐type behavior due to conduction through the SbSe impurity band formed above the valence band maximum, and finally re‐switches to weak p‐type, where the Fermi level approaches the midgap level between the SbSe band and conduction band minimum. Clarification of the Sb doping mechanism will provide a crucial guide for developing more sophisticated doping routes for SnSe and high‐performance energy‐related devices. Abstract : Double charge polarity switching is observed in Sb‐doped SnSe with switchable substitution sites. Pure SnSe shows p‐type conduction, whereas the polarity of (Sn1− x Sb x )Se is switched to n‐type for 0.005 < x  < 0.05, and then re‐switched to p‐type for x  > 0.05, where the major Sb substitution site changes from Se (SbSe ) to Sn site (SbSn ) with increasing x .